Development of an energy management model for Chalmers’ microgrid: Application for cost-benefit analysis of battery energy storage - Göransson, Martin; Larsson, Niklas (My University, 2016)
A microgrid is a portion of a larger grid which can be operated independently, thus it is seen as a single entity from the main grid which can be operated in grid connected or island mode. The microgrid consists of distributed energy resources (DER), energy storage system (ESS) and loads which can be controllable. This thesis is a pre-study regarding Chalmers’ grid as a microgrid. The aim of this thesis is to evaluate the technical and economical performance of Chalmers’ microgrid. In this thesis, a database containing grid data and load profiles for the Chalmers’ grid was established. This database was used as input in the developed energy management model (EMM) for the microgrid, which is a planning model used to schedule and optimize own generation, flexible loads and energy storage within the microgrid. A microgrid simulation platform (MSP) was developed containing the EMM in GAMS and data handling in MATLAB enabling simulations with varying input parameters such as ESS capacity and its location. The MSP is used for benefit-cost analysis of different ESS sizes and locations, and finally for case studies regarding increased amounts of renewable energy (solar PV), island mode operation and vehicle to grid technology (V2G). Results from the analysis show that the total annual cost of electricity can be reduced by 8.43% by including 6 MWh of Li-ion battery storage and increasing the amount of local solar energy to 3 MWp, while also enabling the grid to be operated in island mode for 1 hour periods. With today’s battery prices and expected lifetime, investing in a higher amount of solar PVs and a smaller ESS yields the best investment. The case studies show that running the microgrid in island operation is possible, however to do so for a long time requires a large size of ESS. By running part of Chalmers’ grid as a microgrid, thus having a higher generation to load ratio, the ESS size could be decreased. With increases in renewable energy capacity at Chalmers, the size of batteries to accomplish island-mode operation is reduced. The V2G technology enables the batteries of the vehicles to act as a distributed ESS. The results show that the benefits gained by including electric vehicles are less than the benefits gained by stationary battery storage. This is due to the vehicles being present within the grid during daytime, thus the batteries cannot be charged during the night when electricity prices are lower. There are economical benefits to be gained from operating Chalmers’ grid as a microgrid, however, the investment cost in battery energy storage today is high compared to the benefits gained. Other benefits gained by microgrid operation include enhanced reliability and increased local control. Keywords: Optimal power flow (OPF), Microgrid, Campus, Energy storage system (ESS), Cost-benefit analysis
Keywords: Elkraftteknik; Electric power engineering